México y el TLCAN, veinte años después. - Rouquié, Alain (El Colegio de México A.C., 2015)
This paper discusses the relations between nafta and the following transformations on economics, society, politics, and Mexican policies. This agreement was not an isolated project nor an unexpected shift, but the result of a program of structural reforms that turned the page on the Revolution’s “national popular” model. The treaty continues and ensures the new liberal trend in the Mexican economy. Besides, the transition towards democracy did not suffer major setbacks. The continuity of Mexico’s foreign defensive policies after 1994 and its international influence are also examined.